2009
DOI: 10.1159/000215726
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum CA 19.9, CA 125 and CEA Levels with Severity of Chronic Obstructive Pulmonary Disease

Abstract: Objective: To investigate serum levels of CA 19.9, CA 125 and carcinoembryonic antigen (CEA) in patients with different stages of chronic obstructive pulmonary disease (COPD). Patients and Methods: Fifty-three consecutive patients (50 males, 3 females, mean age 67.6 ± 10.1 years) with COPD were included in this study. Serum levels of CA 19.9, CA 25 and CEA were determined by the chemiluminescent immunometric method. Based on values obtained from pulmonary function tests, the patients were divided into 3 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Hence, CA-125 might help in identification of RV dysfunction, which imposes stress on the splanchnic bed, in patients with COPD before it becomes clinically apparent cor pulmonale. 9,10 Present study included 178 subjects with COPD of which 131 were males (73.6%) and 47 were females (26.4%). The mean age of study subjects was 68.6±9 years and male female ratio was 3.8:1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, CA-125 might help in identification of RV dysfunction, which imposes stress on the splanchnic bed, in patients with COPD before it becomes clinically apparent cor pulmonale. 9,10 Present study included 178 subjects with COPD of which 131 were males (73.6%) and 47 were females (26.4%). The mean age of study subjects was 68.6±9 years and male female ratio was 3.8:1.…”
Section: Discussionmentioning
confidence: 99%
“…Similar study by Bulut ET al in which among 53 patients with COPD, those with cor pulmonale had significantly higher mean serum levels of CA-125, CEA, and CA 19.9 with p < 0.05. 9 Brain natriuretic peptide (BNP) and CA-125 were significantly higher in patients with congestive heart failure than in those without congestive heart failure Another study by Ordu et al in which they measured proBNP and CA-125 in 102 patients with congestive heart failure and concluded that: baseline NT-proBNP and CA-125 levels are comparably reliable as heartfailure markers and suggested that CA-125 can be used for prognosis prediction in heart failure. 10…”
Section: Discussionmentioning
confidence: 99%
“…Bulut et al12 reported that CA 19-9 and CA 125 increased in relation to the severity of chronic obstructive pulmonary disease. However, further study of the association of disease activity with this tumor marker in nonmalignant respiratory disease is required.…”
Section: Discussionmentioning
confidence: 99%
“…CEA is a glycoprotein weight approximately 200,000 dalton. CEA is mainly found in the fetal gastrointestinal tract and in fetal serum (1,2). Secretion of CEA decreases after birth, slight to moderate CEA elevation occurs in benign situations such as in lungs, pancreas, liver disease or in malignant disease in colorectal cancer (3).…”
Section: Introductionmentioning
confidence: 99%